3D Reconstruction of the Morpho-Functional Topography of the Human Vagal Trigone - Emmi, Aron (Front Neuroanat, 2021)
The Vagal Trigone, often referred to as Ala Cinerea, is a triangular-shaped area of the floor of the fourth ventricle that is strictly involved in the network of chardiochronotropic, baroceptive, respiratory, and gastrointestinal control systems of the medulla oblongata. While it is frequently identified as the superficial landmark for the underlying Dorsal Motor Nucleus of the Vagus, this correspondence is not univocal in anatomical literature and is often oversimplified in neuroanatomy textbooks and neurosurgical atlases. As the structure represents an important landmark for neurosurgical procedures involving the floor of the fourth ventricle, accurate morphological characterization is required to avoid unwanted side effects (e.g., bradychardia, hypertension) during neuorphysiological monitoring and cranial nerve nuclei stimulation in intraoperative settings. The aim of this study was to address the anatomo-topographical relationships of the Vagal Trigone with the underlying nuclei. For this purpose, we have conducted an anatomo-microscopical examination of serial sections deriving from 54 Human Brainstems followed by 3D reconstruction and rendering of the specimens. Our findings indicate that the Vagal Trigone corresponds only partially with the Dorsal Motor Nucleus of the Vagus, while most of its axial profile is occupied by the dorsal regions of the Solitary Tract Nucleus. Furthermore, basing on literature and our findings we speculate that the neuroblasts of the Dorsal Motor Nucleus of the Vagus undergo neurobiotaxic migration induced by the neuroblasts of the dorsolaterally located solitary tract nucleus, giving rise to the Ala Cinerea, a topographically defined area for parasympathetic visceral control.